Pension fund investment and firm innovation - Pinkus, David; Pozzoli, Dario; Schneider, Cédric (Journal of Corporate Finance, 2026)
We use a unique dataset on domestic pension fund investments to estimate the relationship between pension fund investment and innovation within Danish unlisted firms. We find a significant positive association between pension fund investment and various measures of innovation, including those targeting green technologies. However, this association is attenuated in highly competitive industries, consistent with a governance channel through which pension funds exert discipline on managers. Overall, our study underscores the important role of pension funds in supporting firm innovation, particularly by reducing managerial slack and by supplying stable, long-term capital to unlisted firms.